Pengaruh Edukasi Terhadap Tingkat Kecemasan Pada Ibu Dalam Menghadapi Menopause Di Kelurahan Oro-Oro Dowo Kota Malang - Devi Ertha Widorini; Surachmindari Surachmindari; Reni Wahyu Triningsih (Akademi Keperawatan Dharma Husada Kediri, 2017)
Menopause is a condition in a woman who has decreased ovarian function resulting in decreased estrogen hormone production so that menstruation stops for good. At menopause women will experience physical or psychological changes. Some mothers believe the myths that develop in the midst of life related to menopause. Therefore, it is expected that menopausal mothers have sufficient knowledge about the life cycle that will be experienced. With sufficient knowledge, then the anxiety in the mother of menopause will be reduced. Knowledge can be obtained through health education in the form of counseling. The purpose of this study was to determine the effect of counseling about menopause on the level of anxiety in menopausal women in the face of menopause. Pre-experimental research design with One Group Pre-post Test Design and using cohort approach. This study used a simple random sampling technique with a sample of 31 menopausal women who met the inclusion criteria. The research instrument using HARS scale consists of 14 closed questions that have been modified. Then the data is analyzed with Wilcoxon Signed Rank Test. The results showed that the significance value of 0,000 then H0 rejected, which means there is influence of counseling about menopause to the anxiety level in menopausal mothers in the face of menopause.